Twórcze, edukacyjne i rozwojowe aspekty aktywności artystycznej osób w wieku późnej dorosłości uczestniczących w terapii zajęciowej w Dziennych Domach Pomocy Społecznej - Sienkiewicz-Wilowska, Julia Anastazja (Wydawnictwo Naukowe UAM, 2016)
The article discusses the educational, improving and preventive role of creative activities in the activation of the elderly. The considerations are based on results of studies on these activities. The paper analyzes the artistic activities conducted within the framework of occupational therapy in day-time nursing homes (in the city of Poznan). Issues related to artistic activities organized at the Universities of the Third Age and informal education are also included.
Creative, Educational and Developmental Aspects of Artistic Activity of People in Their Late Adulthood Participating in Occupational Therapy in Day-Time Nursing Homes
Keywords: creation; creativity; elderly people; occupational therapy